Does M&A create value for bidding companies?-----Empirical Studies from UK companies - Ye, Xin (2007)
The complex phenomenon that mergers and acquisitions (M&A) represent has attracted substantial interest from a variety of management disciplines over the past 30 years. Past literatures on M&A points out that there are various motives for undertaking a merger or an acquisition which lead to value conservation, creation or deduction of two entities namely the firm and the shareholder. Reviewing relevant studies suggest that while targeted firm shareholders generally enjoy positive short-term returns, shareholders in bidding firms frequently surfer share price underperformance. This dissertation aimed to examine how M&A affect shareholders value of acquiring firms and what are the factors lead to value-creation and deduction.